2011
DOI: 10.1002/adem.201080092
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Photopolymerizable Hydrophilic Macromers and Evaluation of Their Applicability as Reactive Resin Components for the Fabrication of Three‐Dimensionally Structured Hydrogel Matrices by 2‐Photon‐Polymerization

Abstract: Two‐photon polymerization (2‐PP) is a promising new photolithographic technique to fabricate three‐dimensional (3D), micro‐ and nano‐structured tissue engineering scaffolds from photopolymerizable monomers. Although various photo resins are known for the use in 2‐PP, there is currently a need for photo‐curable monomers processable by 2‐PP to generate biocompatible 3D‐structured hydrogel materials for soft or cartilage tissue regeneration. In the present work hydrophilic methacrylate monomers and macromers base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…In the research field of bone regeneration based on photopolymerized hydrogels groups show interesting scaffold specimens with high potential in regenerative medicine . Hydrogel scaffolds can easily be formed via photo‐initiated polymerization, as for instance shown for the preparation of PEGDA scaffolds by dynamic photomask micro‐stereolithography or two‐photon polymerization . Fairbanks et al demonstrate that human mesenchymal stem cells proliferate well on hydrogel structures .…”
Section: Introductionmentioning
confidence: 99%
“…In the research field of bone regeneration based on photopolymerized hydrogels groups show interesting scaffold specimens with high potential in regenerative medicine . Hydrogel scaffolds can easily be formed via photo‐initiated polymerization, as for instance shown for the preparation of PEGDA scaffolds by dynamic photomask micro‐stereolithography or two‐photon polymerization . Fairbanks et al demonstrate that human mesenchymal stem cells proliferate well on hydrogel structures .…”
Section: Introductionmentioning
confidence: 99%
“…As previously reported, hydrogels prepared from D-MA in a conventional radical polymerization initiated thermally (298 K, ammonium peroxodisulfate/ N,N,N',N'tetramethylethylene diamine or potassium peroxodisulfate/ triethanolamine) (Möller et al 2007) or photochemically (eosin Y/triethanolamine initiation system) (Berg et al 2011) were investigated in respect to their biodégradation behavior. It was found that thermal and photochemical polymerization under the given conditions results in hydrogels, which slowly degraded in simulated body fiuid (SBF) medium.…”
Section: Discussionmentioning
confidence: 99%
“…But, this can cause unknown changes in the material characteristics due to the enhanced concentration of incorporated PI. [11] Several donor-p-donor and donorp-acceptor-p-donor systems, [11,22,23] similar as various acetophenons [24][25][26] have been proven to be efficient PIs for TPP. [17,18] When it comes to the application of the generated constructs in biomedical applications, initiator migration issues have been considered.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] In principle, the migration can occur by set-off, by diffusion, and by gas-phase transport. [24,25,35] 2.1.1. For example, one route for acetophenone based PIs, like Irgacure 369 (IC369), is to generate their own scission products (type I), which are in this case small aromatic radicals that can react to potentially harmful side products.…”
Section: Introductionmentioning
confidence: 99%